2022
DOI: 10.1590/s1678-9946202264054
|View full text |Cite
|
Sign up to set email alerts
|

First case report of monkeypox in Brazil: clinical manifestations and differential diagnosis with sexually transmitted infections

Abstract: In 2022, an outbreak of monkeypox is being reported in non-endemic areas, with unusual clinical manifestations. The detailed clinical description of the first patient that received the diagnosis of monkeypox in Brazil is reported here, whose clinical manifestations can easily lead to misdiagnosis of sexually transmitted infections. A 41 years old male presented to an emergency room with a vesicular rash with eight days of evolution. He had traveled to Portugal and Spain and reported non-penetrative sexual invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
0
11
0
6
Order By: Relevance
“…After the removal of duplicates ( n = 566), 456 articles were screened by the authors. After filtering the titles and reading the abstracts, 85 articles were selected for full-text reading, and 65 were considered eligible for inclusion in this systematic review ( Figure 1 ) [ 18 , 20 , 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the removal of duplicates ( n = 566), 456 articles were screened by the authors. After filtering the titles and reading the abstracts, 85 articles were selected for full-text reading, and 65 were considered eligible for inclusion in this systematic review ( Figure 1 ) [ 18 , 20 , 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ,…”
Section: Resultsmentioning
confidence: 99%
“…The review included 65 studies published between 1 January and 5 October 2022. The studies ( n = 65) reported monkeypox case reports according to the specimen collection site, the number of cases, sexual behavior-oriented risk factor, history of sexually transmitted diseases, site of specimen drawn and positive for monkeypox virus by PCR, location of skin lesions, and method of diagnosis were described in detail ( Table 2 ) [ 18 , 20 , 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No Brasil, a primeira notificação da varíola dos macacos se deu no dia 09 de junho de 2022, no município de São Research, Society andDevelopment, v. 11, n. 15, e384111537525, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i15.37525 Paulo (Lima et al, 2022). A partir de então, mesmo com as recomendações instituídas pelo Ministério da Saúde, tais como conscientização das comunidades e capacitação dos profissionais de saúde, para evitar a propagação do vírus, o país apresentou cerca de 8.652 casos da enfermidade, com 8 óbitos, até o dia 16 de outubro de 2022 (Schrarstzhaupt et al, 2022).…”
Section: Introductionunclassified